2005
DOI: 10.1177/021849230501300422
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Systemic Inflammatory Response after Cardiac Surgery

Abstract: Cardiac surgery and cardiopulmonary bypass initiate a systemic inflammatory response largely determined by blood contact with foreign surfaces and the activation of complement. It is generally accepted that cardiopulmonary bypass initiates a whole-body inflammatory reaction. The magnitude of this inflammatory reaction varies, but the persistence of any degree of inflammation may be considered potentially harmful to the cardiac patient. The development of strategies to control the inflammatory response followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 196 publications
(217 reference statements)
0
67
0
2
Order By: Relevance
“…7 Additionally, the magnitude of the systemic and tissue inflammatory process, assessed by measurement of these specific biomarkers may reflect the risk of postoperative complications and progression of the contralateral carotid disease. 7 Raja et al 12 claim that the systemic inflammatory response after cardiovascular surgery is due to ischemia-reperfusion injury to target organs caused by clamping of arteries and restoration of perfusion after release of the hemostatic forceps. Additionally, persistence of an elevated degree of postoperative inflammation can potentially be prejudicial to patients subjected to cardiovascular surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Additionally, the magnitude of the systemic and tissue inflammatory process, assessed by measurement of these specific biomarkers may reflect the risk of postoperative complications and progression of the contralateral carotid disease. 7 Raja et al 12 claim that the systemic inflammatory response after cardiovascular surgery is due to ischemia-reperfusion injury to target organs caused by clamping of arteries and restoration of perfusion after release of the hemostatic forceps. Additionally, persistence of an elevated degree of postoperative inflammation can potentially be prejudicial to patients subjected to cardiovascular surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, persistence of an elevated degree of postoperative inflammation can potentially be prejudicial to patients subjected to cardiovascular surgical interventions. 12 However, Rubens et al 13 and Liguori et al 14 have concluded that the systemic inflammatory response is variable and can be influenced by patient comorbidities; intraoperative non-pharmacological interventions; type of anesthesia; perioperative hemodynamic conditions; surgical aspects (surgical incision, duration of the procedure, duration of arterial clamping and need for blood transfusion); and postoperative recovery. In order to ensure that the same perioperative conditions prevailed, we standardized general anesthesia and classical endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Table 4 lists the vast majority of potential pharmacologically useful agents. Raja and Dreyfus (2005) superbly describe all these curbing alternatives, which is a recommended reader 6 . The current literature on worldwide cardiac surgery excellence supports the overestimation of pathological inflammation in human CPB surgery.…”
Section: Curbing Cardiopulmonary Bypass Inflammationmentioning
confidence: 99%
“…Neben Endotoxin sind auch Ischämie sowie Komplementaktivierung Stimuli der Zytokinfreisetzung [19]. Während der EKZ kommt es insbesondere zu erhöhten Interleukin(IL)-6-und IL-8-Spiegeln.…”
Section: Zytokineunclassified